The dispute over the social license for mining projects in La Rioja, Argentina - Sola Álvarez, Mariana (2013)
Since the beginning of this century, projects of transnational corporations design to extract -in a mega scale- gold, silver, copper, and molybdenum are back to interrogate Famatina Valley, located in the northwest of Argentina, in the province of La Rioja. The dispute that is generated around the "social license" of mining projects highlights features of policy matrix and local government backing for extractive activities. At the same time illustrates the content and the potentiality of social resistance. The power of veto from a network of neighbors assemblies and a highly mobilized community in critical moments of the conflict is framed in a process of resistance to mercantilization of commons that travels through Latin America.